Fate of a Naive T Cell: A Stochastic Journey - de la Higuera, Luis; López-García, Martín; Castro, Mario; Abourashchi, Niloufar; Lythe, Grant; Molina-París, Carmen (Frontiers in Immunology, 2019)
The homeostasis of different T cell sub-populations depends on migration, division and death of individual cells. T cells migrate between spatial compartments (e.g., blood, spleen, lymph nodes, lung, liver, etc.), divide or differentiate during their stay in these compartments, and eventually die. The kinetics of this recirculation influences the speed at which local infections are detected and controlled (1). New experimental techniques have been developed to measure the lifespan of cells, and their migration dynamics; for example, fluorescence-activated cell sorting (2), in vitro time-lapse microscopy (3), or in vivo stable isotope labelling (e.g., deuterium) (4). When combined with mathematical and computational models, they allow estimation of rates of migration, division, differentiation and death (5). In this work, we consider a stochastic model of a single cell migrating between spatial compartments, dividing and eventually dying. We calculate the number of division events during a T cell’s journey, its lifespan, the probability of dying in each compartment and the number of progeny cells. A rapid-migration approximation allows us to compute these quantities when migration rates are much higher than division and death rates. Making use of published rates: (i) we analyse how perturbations in a given spatial compartment impact T cell dynamics, (ii) we study the accuracy of the rapid-migration approximation, and (iii) we quantify the role played by direct migration (not via the blood) between some compartments.